Supporting people with learning disabilities through a bereavement. Issue 4 (3rd October 2016) - Blackman, Noelle
Abstract : Purpose: There remains a lack of clarity regarding what constitutes "normal" or "complicated" grief within this client group. The purpose of this paper is to identify the factors that complicate grief and considers interventions which would be beneficial. Design/methodology/approach: The paper draws on previous research by the author and others to comment on some of the issues discussed by Hannah Young in her article. Findings: Three domains contribute to complicated grief in people with learning disabilities. These are the learning disability itself, environmental factors and the impact of disability on attachment. Practical implications: A relational approach to support is important in preventing complicated grief. If the grief becomes complicated, a relational psychotherapy is recommended as the preferable intervention. Originality/value: This paper gives important consideration to practical factors that can lower vulnerability to complicated grief for this client group.